Investigation of hydrodynamics and convection in the porous car heat exchanger. Issue 1 (September 2020) - Soloveva, O V; Solovev, S A; Khusainov, R R; Yafizov, R R
Abstract: Car engine cooling is actual problem today. The work considers the gas flow in aluminium open cell foam material with two different values of the porosity of the medium 0.9 and 0.7. Models of porous media with an ordered and random structure have been created; in both cases, the porous medium is constructed by a set of intersecting spheres. Numerical modelling of gas flow and heat transfer in a porous medium is carried out using the control volume method in the ANSYS Fluent software package (v. 19.0). The results of the calculation of the pressure drop correlate well with the results of calculations obtained by the semi-empirical dependence. Given the best mixing of the flow, convective heat transfer is more intense in the model of a porous medium with a random arrangement of cells. The highest porosity of medium 0.9 provides the lowest pressure drop and increases the value of heat transfer. It has been shown that in a porous medium of any geometry, the Nusselt number increases with increasing Reynolds number. In this case, open cell foam with a random arrangement of pores in space and a maximum porosity of the medium is preferred for use as a heat exchanger in transport.